Milk SCC levels impact on fertility indicators in Ayrshire cows - Komlyk Irina; Lepesheva Irina (BIO Web of Conferences)
The paper examined the associative links affecting the fertility indicators of cows. The study was conducted in one of the highly productive herds for breeding Ayrshire cattle (milk yield level of 8000−9000 kg of milk). Based on the data of 3866 lactations, we analyzed the following reproduction indicators: indifference period, conception rate after the first insemination, early embryonic mortality, insemination period, insemination index, service period. We carried out an indirect assessment of the state of the udder in cows based on the somatic cell count (SCC) in milk. The age of the cows was considered as a factor of the SCC variability. We analyzed the relationship between the somatic cell level and reproductive indicators. We found that the milk yield and somatic cell content in milk increase in cows with age. We found a curvilinear relationship between productivity and SCC in milk. The study established that the level of somatic cells affects the reproductive indicators. Cows with a healthy udder (SCC < 100 thousand / ml), compared to conditionally healthy ones (SCC < 300 thousand / ml), became pregnant more often after the first insemination, had a lower insemination index and a level of early embryonic mortality.